Two decades of single-institution data reveal rare long-term survivors of relapsed/refractory Burkitt lymphoma - Rabeya Molla; Kurt Bantilan; Ellin Berman; Philip Caron; Lorenzo Falchi; Paul Hamlin; Steven Horwitz; Andrew Intlekofer; Anita Kumar; Jennifer Lue; Alison Moskowitz; Colette Owens; et al. (Haematologica)
Not available.